Dynamic flux balance analysis of a genetic engineered cyanobacterium for ethanol production - Laiglecia, Juan Ignacio (2013)
Fil: Laiglecia, Juan Ignacio. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química (PLAPIQUI), CONICET. Bahía Blanca, Argentina